f ( x ) is a polynomial that satisfies f ( x + y ) = f ( x ) + f ( y ) + 3 x y for all real numbers x and y . If f ′ ( 0 ) = 3 5 , what is the value of f ( 2 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i tried in ds way
By differentiating both side w.r.t. x , we obtain f ′ ( x + y ) = f ′ ( x ) + 3 y . Continue differentiating both sides w.r.t. y , we deduce that f ′ ′ ( x + y ) = 3 . Hence f ′ ′ ( x ) = 3 for all x . Then f ′ ( x ) = 3 x + c . Since f ′ ( 0 ) = 3 5 , c = 3 5 , and then f ( x ) = 2 3 x 2 + 3 5 x + d . By using the assumption f ( x + y ) = f ( x ) + f ( y ) + 3 x y , we deduce that d = 0 . Therefore, f ( x ) = 2 3 x 2 + 3 5 x and f ( 2 ) = 7 6 .
First, we find f ( 0 ) . $$f(0+0)=f(0)+f(0)+3(0)(0)$$ $$f(0)=2f(0)$$ $$f(0)=0$$ We know a value of the derivative of f , so it would likely be helpful to take the derivative of f . However, we need to get f in terms of one variable, so we fix y = c . So, we have $$f(x+c)=f(x)+f(c)+3xc.$$ Differentiating, we get $$f'(x+c)=f'(x)+3c$$ because c is a constant. Differentiating again, we have $$f''(x+c)=f''(x).$$ Because this holds for any constant c , we have that f ′ ′ ( x ) is constant. In other words, $$f''(x)=a,$$ for some constant a . Integrating, we get $$f'(x)=ax+b,$$ for some constant b . Because we know f ′ ( 0 ) = 3 5 , we have b = 3 5 . So, $$f'(x)=ax+35.$$ Integrating again, we get $$f(x)=\frac{a}{2}x^2+35x+k,$$ for some constant k . We know f ( 0 ) = 0 , so k = 0 and $$f(x)=\frac{a}{2}x^2+35x.$$ To find out the value of a , we observe $$f(0)=f(x+(-x))=f(x)+f(-x)-3x^2=0.$$ Thus, $$f(x)+f(-x)=3x^2.$$ Applying this fact to our equation f ( x ) = 2 a x 2 + 3 5 x gives $$\left( \frac{a}{2}x^2 +35x \right) + \left( \frac{a}{2}x^2 -35x \right) = ax^2 = 3x^2.$$ Thus a = 3 , and so $$f(x)=\frac{3}{2}x^2+35x$$ and $$f(2)=\frac{3}{2}(2)^2+35(2)=\fbox{76}.$$
Since f ′ ( 0 ) is given to us, we aim to find an equation involving f ′ ( x ) and the simplest way is to differentiate both sides of the given equation. Taking the partial derivative with respect to x on both sides of the equation, we have f ′ ( x + y ) = f ′ ( x ) + 3 y and substituting x = 0 we get f ′ ( y ) = f ′ ( 0 ) + 3 y = 3 5 + 3 y as given. Now, integrating both sides with respect to y gives us f ( y ) = 2 3 y 2 + 3 5 y + C where C is some constant.
Substituting this back to the original equation gives us 2 3 ( x + y ) 2 + 3 5 ( x + y ) + C = 2 3 x 2 + 3 5 x + C + 2 3 y 2 + 3 5 y + C + 3 x y and cancelling like terms on both sides gives C = 2 C ⇒ C = 0 and hence f ( x ) = 2 3 x 2 + 3 5 x so f ( 2 ) = 2 3 2 2 + 3 5 ( 2 ) = 7 6
Let polynomial
f ( x ) = a n x n + a n − 1 x n − 1 + … + a 2 x 2 + a 1 x + a 0 ,
Then,
f ( y ) = a n y n + a n − 1 y n − 1 + … + a 2 y 2 + a 1 y + a 0 , and
f ( x + y ) = a n ( x + y ) n + a n − 1 ( x + y ) n − 1 + … + a 2 ( x + y ) 2 + a 1 ( x + y ) + a 0
Using the given equation, f ( x + y ) = f ( x ) + f ( y ) + 3 x y
We get f ( x + y ) − ( f ( x ) + f ( y ) ) = 3 x y
a n ( ( x + y ) n − ( x n + y n ) ) + … + a 2 ( ( x 2 + y 2 + 2 x y ) − ( x 2 + y 2 ) ) + a 1 ( ( x + y ) − ( x + y ) ) + a 0 − 2 a 0 = 3 x y
Since there is only term of x y , and not x 2 y , x y 2 , etc on the RHS, therefore the value of n = 2
From the above equation, we get a 0 − 2 a 0 = 0 , therefore the constant term of f ( x ) , a 0 = 0
Also equating the x y term gives 2 a 2 x y = 3 x y
a 2 = 2 3
f ( x ) can be rewritten as 2 3 x 2 + a 1 x + 0
Here I will be replacing a 1 , with a . So,
f ( x ) = 2 3 x 2 + a x
Differentiating f ( x ) will give
f ′ ( x ) = 2 3 × 2 x + a
f ′ ( x ) = 3 x + a
Since f ′ ( 0 ) = 3 5 ,
3 × 0 + a = 3 5
a = 3 5
Now we know
f ( x ) = 2 3 x 2 + 3 5 x
Therefore,
f ( 2 ) = 2 3 × 2 2 + 3 5 × 2
f ( 2 ) = 6 + 7 0
f ( 2 ) = 7 6
very very very very very lengthy&borin
putting x=y=0 we get,f(0)=0...now put x=x and y=h....f(x+h)=f(x)+f(h)+3xh now...(f(x+h)-f(x))/h=(f(h)-f(0))/h+ 3x...and h tends to 0....the equation becomes..f '(x)=f '(0)+3x=35+3x..after integrating..f(x)=35x+1.5x^2+c...c=0 as f(0)=0....f(2)=76!!
Firstly, check for x=y=0 in the given polynomial expression,
f(0)= f(0)+ f(0) ===>f(0)= \boxed{0}
Now, we know that,
*f'(x) = limit(h \rightarrow 0) \frac {f(x+h)- f(x)}{h} *
Simplifying above, we obtain,
f'(x)
= limit(h\rightarrow0) \frac {[f(x) + f(h) + 3hx] -f(x) }{h}
= limit(h\rightarrow0) \frac {f(h) + 3hx}{h}
= limit(h\rightarrow0) \frac {3hx + f(h) - f(0)}{h}
= limit(h\rightarrow0) \frac { 3x + \frac {f(h)-f(0)}{h}}
Since, limit(h\rightarrow0) \frac {f(h)-f(0)}{h} = f'(0), we have,
f'(x) = 3x + f'(0) = 3x +35
\Rightarrow f(x) = 3/2 x^2 + 35x ... (since we get the constant of integration as 0 by using the condition f(0)=0)
Thus, \boxed{f(2)=76}
Guys, please help in Latex, moderator please...
Differentiating f(x+y) = f(x) + f(y) + 3xy with respect to x we get,
f'(x+y) = f'(x) + 3y
Now, put x=0. We get f'(y) = 3y + 35.
Integrating this equation we get, f(y) = 3/2 y^2 + 35y+ C, ............(i) where C is the constant of integration .
Putting x=y=0 in the original functional equation, we get that f(0)=0.
Putting y=0 in (i) we get f(y) = 3/2 y^2 + 35y
Putting y=2 in (i) we get, f(2) = 76.
f(2) = 76 is the required answer.
f'(x+y)=f'(x)+3y put x=0,y=x then
f'(x)=35+ 3x
y=35x+ 3x*x/2 +c
since f(0)=0
c=0
f(2)=76
Problem Loading...
Note Loading...
Set Loading...
Substitute x = 0 and y = 0 in the given functional equation to get f ( 0 ) = 0 .
Since,
f ′ ( x ) = h → 0 lim h f ( x + h ) − f ( x ) = h → 0 lim h f ( x ) + f ( h ) + 3 x h − f ( x )
⇒ f ′ ( x ) = h → 0 lim h f ( h ) + 3 x h
Substituting h = 0 gives 0/0 hence, apply l'Hôpital's rule.
⇒ f ′ ( x ) = h → 0 lim f ′ ( h ) + 3 x = 3 x + 3 5
Solving the differential equation and using the initial condition that f ( 0 ) = 0 , we have
f ( x ) = 2 3 x 2 + 3 5 x ⇒ f ( 2 ) = 7 6